2002
DOI: 10.1021/jp013697z
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Stimulated Chemical Reactions in Carbon Tetrachloride/Water (Ice) Films

Abstract: The electron-stimulated chemical reactions in carbon tetrachloride/water (ice) and ice films have been studied using reflection-absorption infrared spectroscopy (RAIRS) and mass spectrometry. CO 2 , CO, and HCl were identified as the final neutral reaction products in the electron-stimulated degradation of CCl 4 , while COCl 2 and C 2 Cl 4 were produced as intermediates. Molecular H 2 and O 2 were detected as neutral gas-phase products in the electron beam irradiation of pure ice films. Production of molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 57 publications
4
52
0
Order By: Relevance
“…The CO 2 , COCl 2 , H 3 O þ and H x D 3 À x O þ intensities grow to maxima and then decrease upon prolonged electron irradiation. This growth and decrease of the carbon-containing products COCl 2 and CO 2 upon electron irradiation is qualitatively similar to that seen for CCl 4 /water films [39]. Negative absorption peaks observed between 3600-3000 and 920-730 cm À1 are due to the electron-stimulated consumption of both H 2 O and CDCl 3 .…”
Section: Product Identification During Irradiation Of Cdcl 3 /Water Fsupporting
confidence: 79%
See 1 more Smart Citation
“…The CO 2 , COCl 2 , H 3 O þ and H x D 3 À x O þ intensities grow to maxima and then decrease upon prolonged electron irradiation. This growth and decrease of the carbon-containing products COCl 2 and CO 2 upon electron irradiation is qualitatively similar to that seen for CCl 4 /water films [39]. Negative absorption peaks observed between 3600-3000 and 920-730 cm À1 are due to the electron-stimulated consumption of both H 2 O and CDCl 3 .…”
Section: Product Identification During Irradiation Of Cdcl 3 /Water Fsupporting
confidence: 79%
“…The experiments that are the focus of this article were carried out in three different ultrahigh vacuum (UHV) systems [36][37][38][39][40][41]. Figure 1 represents the schematic of a virtual (generalized) set-up that illustrates the instrumentation used in these chambers for characterization of the surface structure, composition and reactivity of thin films containing halogenated compounds.…”
Section: Methodsmentioning
confidence: 99%
“…An unsaturated compound is a good radical trap and may act as a seed for the initiation of polymer formation with any other carbon centered radical. Carbene radicals are reported to be an intermediate product in CCl 4 -water (ice) films [35] and in heme/TiO 2 [36], but their existence in aqueous solutions is unknown. Other oxygen containing products like HCHO, HCOOH, CO and CO 2 are also reported in the radiolysis of chloromethanes [8,9,13].…”
Section: Resultsmentioning
confidence: 99%
“…There are also other studies of electron induced reactions of condensed CF identified by RAIRS (C-Cl) and (C-F) peaks, respectively [101,102]. For instance, about 10% of CF 2 Cl 2 remained on the surface with extended exposure of the X-ray source by 500 min [102].…”
Section: Other Measurementsmentioning
confidence: 98%
“…For instance, about 10% of CF 2 Cl 2 remained on the surface with extended exposure of the X-ray source by 500 min [102]. The secondary electron current generated such a X-ray source is typically in the order of [101] stated that "the same chemical transformations (reaction products) were observed for CCl 4 /H 2 O (ice) films using the X-ray source or the electron gun in the absence or presence of an applied bias voltage (+200)".…”
Section: Other Measurementsmentioning
confidence: 99%